Functionality of Service-oriented Institutions Vis-à-vis Rural Development Situation in Eastern Samar, Philippines - Hilarion A. Odivilas (European Scientific Journal, ESJ, 2016)
This study ascertained the functionality of service-oriented institutions in relation to rural development situation in Eastern Samar. It aimed to: (a) determine the perceptions of the rural poor on the functionality of identified institutions in terms of their assistance extended and the type of benefits derived, (b) analyze the development situation of the municipalities of Eastern Samar in terms of socio-economic status, health conditions, education and training and peace situation, and (c) evaluate the relationship between the perceived functionality of the institutions and the development situation of Eastern Samar. The study utilized the descriptive-correlational design, with the use of an interview guide, in order to determine the functionality of the identified institutions and the development situation of the different municipalities of the province using Mean and Pearson Productmoment Coefficient Correlation. Government organizations, nongovernment organizations, community organizations and local government units had functional performance in development projects. However, the assistance extended by different agencies perceived to be highest did not consistently provide the highest benefits. These brought about by the organizations’ resource capabilities, extent of implementation and the choice of the beneficiaries. The similarity of community needs and resources and the scope of the organizations’ objectives influenced the similarity of activities in the barangays. Other NGOs, community organizations and local government units performed similarly in all barangays. Majority of the respondents had low income and lived in wooden type of houses, had fair health conditions, finished elementary education enough to have the ability to read and write. A greater majority of the respondents’ children of school age were in school. With peaceful communities in Eastern Samar, low criminality rate and low presence of communist-oriented elements contributed to the development assistance extended by the LGUs in terms of education and livelihood projects.